2019
DOI: 10.1016/j.jenvrad.2019.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative overview of indoor radon surveys in Europe

Abstract: The revised European Directive from 2013 regarding basic safety standard oblige EU Member States to establish a national action plan regarding the exposure to radon. At the same time, International Atomic Energy Agency started technical projects in order to assist countries to establish and implement national radon action. As a consequence, in recent years, in numerous countries national radon surveys were conducted and action plans established, which were not performed before. In this paper, a qualitative ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 64 publications
0
31
0
1
Order By: Relevance
“…The primary dataset used to predict the mean per grid cell with no or few data is the one of arithmetic means (AM_z). The AM was assigned to the centre of each grid cell, and predictions were carried out only in grid cells where U, Th, and K 2 O concentrations were also available (46 000 grid cells; version 28-05-2018, Pantelić et al, 2018). Data from grid cells filled by more than one country (i.e.…”
Section: Indoor Radon Datamentioning
confidence: 99%
“…The primary dataset used to predict the mean per grid cell with no or few data is the one of arithmetic means (AM_z). The AM was assigned to the centre of each grid cell, and predictions were carried out only in grid cells where U, Th, and K 2 O concentrations were also available (46 000 grid cells; version 28-05-2018, Pantelić et al, 2018). Data from grid cells filled by more than one country (i.e.…”
Section: Indoor Radon Datamentioning
confidence: 99%
“…The primary dataset used to predict the mean per grid cell with no or few data is the one of arithmetic means (AM_z). The AM was assigned to the centre of the grid cell, and predictions were carried out only in grid cells where U, Th, and K 2 O concentrations also were available (46,000 grid cells; version 28-05-2018, Pantelić et al, 2018). Data from grid cells filled by more than one country (i.e.…”
Section: Indoor Radon Datamentioning
confidence: 99%
“…A World Health Organization (WHO) survey of 36 countries found that almost all countries have set reference levels for existing housing between 200 Bq m -3 and 400 Bq m -3 [1], and some countries have set lower reference levels for new houses (200 Bq m -3 ) than for existing buildings [3]. According to the 2013 Basic Safety Standards (BSS) Directive -Directive 2013/59/Euratom, European member states are required to have a radon action plan and inform the population about the radon levels [4].…”
Section: Introductionmentioning
confidence: 99%
“…Indoor radon (concentration) levels were recently measured in fifty workplaces in Albania exceeding the radon national reference of 300 Bq m -3 in one workplace in Tirana [9]. The fifty-four percent of Tirana urban area is made of soils containing high soil gas radon concentration (above > 30 KBq m -3 ) [4]. Yet, surveys to assess the extent of the public knowledge about indoor radon and indoor radon level measurements are in need.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation